High-performance triboelectric nanogenerators based on Ag-doped ZnO loaded electrospun PVDF nanofiber mats for energy harvesting and healthcare monitoring - Hema Malini Venkatesan; Anand Prabu Arun (Scientific Reports)
Abstract This study investigates the potential of zinc oxide (ZnO) and Ag-doped zinc oxide (Ag-ZnO) nanoparticles (NPs) (1, 3 and 5 wt%) electrospun into poly(vinylidene fluoride) (PVDF) based triboelectric nanogenerators (TENGs) to harness electrical energy from ambient mechanical vibrations. ZnO and Ag-ZnO NPs were developed using a co-precipitation method. 3 wt% Ag-ZnO doping was optimized to exhibit a higher β-crystalline phase in PVDF (PAZ3). The electrospun ZnO and Ag-ZnO loaded PVDF nanofiber mats (NFMs) served as tribo-negative layer, while thermoplastic polyurethane (TPU) served as tribo-positive layer in the TENG device fabrication. The electrical measurement results revealed that pristine PVDF/TPU-based TENG device exhibited lower performance (V oc = 9.0 V and I sc = 0.6 µA) compared to the optimized PAZ3/TPU-based TENG (V oc = 51 V and I sc = 1.2 µA), and utilized for concurrent applications such as powering over 10 light-emitting diodes, energy harvesting and healthcare monitoring applications. Overall, the study not only reveals the significant potential of PAZ3/TPU-based TENG for excellent output performance, but also provides a new insight into next-generation clean, affordable and sustainable energy harvesting materials.